Updating the relationship of the Ne/ERN to task-related behavior: A brief review and suggestions for future research - LoTemplio, Sara B.; Lopes, Clara Louise; McDonnell, Amy S.; Scott, Emily E.; Payne, Brennan R.; Strayer, David L. (Frontiers in Human Neuroscience, 2023)
The error negativity/error-related negativity (Ne/ERN) is one of the most well-studied event-related potential (ERP) components in the EEG literature. Peaking about 50 ms after the commission of an error, the Ne/ERN is a negative deflection in the ERP waveform that is thought to reflect error processing in the brain. While its relationships to trait constructs such as anxiety are well-documented, there is still little known about how the Ne/ERN may subsequently influence task-related behavior. In other words, does the occurrence of the Ne/ERN trigger any sort of error corrective process, or any other behavioral adaptation to avoid errors? Several theories have emerged to explain how the Ne/ERN may implement or affect behavior on a task, but evidence supporting each has been mixed. In the following manuscript, we review these theories, and then systematically discuss the reasons that there may be discrepancies in the literature. We review both the inherent biological factors of the neural regions that underlie error-processing in the brain, and some of the researcher-induced factors in analytic and experimental choices that may be exacerbating these discrepancies. We end with a table of recommendations for future researchers who aim to understand the relationship between the Ne/ERN and behavior.